The Aswan Rheumatic heart disease reGIstry: rationale and preliminary results of the ARGI database - Kotit, Susy; Yacoub, Magdi H. (Frontiers in Cardiovascular Medicine, 2023)
Background: Rheumatic Heart Disease (RHD) remains a major cause of valvular heart disease related mortality and morbidity in low-and middle-income countries, with significant variation in characteristics and course of the disease across different regions.However, despite the high disease burden, there is sparse region-specific data on demographics, disease characteristics and course in treated and untreated patients to guide policy.The ARGI database is a hospital-based registry in a tertiary referral national centre (Aswan Heart Centre, AHC) in which all patients with the diagnosis of RHD are being included. The mode of presentation, including baseline clinical and echocardiographic characteristics (as well as other imaging modalities), biomarkers and genetics are being documented. Treatment modalities and adherence to treatment is being recorded and patients are followed up regularly every 6 and/or 12 months, or more frequently if needed.This study shows for the first time an in-depth analysis of the severity and phenotype of disease in Egyptian patients presenting with RHD as well as the progression with time and provides a platform for further comparisons of regional differences in these details as well as their causes. The ARGI database will be of help in achieving the objectives of the Cairo Accord aiming at eradication of RF and RHD.